BAGAIMANA BRAND LOVE MEMEDIASI PENGARUH BRAND EXPERIENCE TERHADAP LOYALITAS KONSUMEN PADA PRODUK LABEL SUKLA ? - Desak Made Febri Purnama Sari; Ni Ketut Mira Ayu Agustin; Putu Ayu Titha Paramitha Pika; Ida ayu Oka Martini (Jurnal MBE Manajemen Bisnis, Equilibrium, 2026)
Abstract: This study aims to examine the influence of brand experience on brand loyalty and brand love in mediating the influence of brand experience on brand loyalty for Sukla-labeled products in Bali. This study was conducted to analyze the behavior of consumers who have made decisions to purchase food products labeled Sukla, with a focus on aspects of brand experience that can influence the level of brand love. The sample in this study was 120. This research approach was quantitative, analyzed using Structural Equation Modeling (SEM). The results of this study indicate that brand experience has a very positive influence on the level of brand love among customers who are the sample of the study. Specifically, the impact of this brand experience was recorded at 87.2%, indicating that the better the consumer experience with the brand, the greater their level of love for the brand. The findings suggest a marketing strategy that focuses on improving brand experience to build strong long-term relationships with consumers. Brand experience has a very significant influence on brand love. The implications of the results of the study suggest that businesses with the Sukla label must create good experiences to develop feelings of love for the brand. Theoretically, this study adds to the literature on the importance of branding using labels to increase consumer trust.